A field survey of local value of the protected sycamore tree line of Gödöllő, Hungary (2014) - Berecz, Tibor; Fehér, Luca; Gyovai, Gábor; Hága, Krisztián; Kazinczy, István Gábor; Kiszel, Kata Zsófia; Mészáros, Melinda Márta; Morvai, Edina; Pápay, Gerg; Petrovszki, János; Prohászka, Viola Judit; Raffa, Brigitta; et al. (JOURNAL OF LANDSCAPE ECOLOGY, 2015)
Locally protected areas of Hungary have an important role in nature conservation, especially in curating values of nature among locals. There are several locally protected nature areas in Gödöllő but up until now, there hasn’t been much information generated around them. Currently, the sycamore-tree line in Gödöllő is under significant human threat, thus inspiring this field survey. The data recorded here is compared to the data collected by the Szent István University in 2013. The answers to the survey questions addressed the possibility of creating a management plan for this local natural area. The survey was conducted by measuring the distances from the road and fences to the trees and the distances between the individual trees, the perimeters of the trees at ground level, and at 140-, 160- and 180 cm of height. The research also included the individual trees’ health in relation to human impact, in which the street traffic, compaction and rate of litter was examined. It was determined that the protected tree line is under significant human pressure and the following actions/precautions should take place in order to conserve this natural area: The missing trees and the boards should be replaced; the parking lot in the area should be moved to a less impeding location; wastebins should be placed in the area to reduce litter; educational information kiosks should be constructed in the area to provide knowledge for locals and visitors; and finally, environmental education should be implemented at the elementary level – following the National Master Plan – increasing the responsibility of young people and their understanding of nature and the values of nature.
Keywords: change of state; nature conservation; student survey; protected tree line